Neuronal deletion of PDE7A averts morphine-induced behavioral plasticity and impairs downstream AKT signaling - Zizhen Liu; Axiang Li; Chengyou Zheng; Ruyan Gao; Kaiwu He; Zhen Tan; Tahir Ali; Liangliang Hao; Tao Li; Shupeng Li (Molecular Biology Reports, 2026)

Flocculation performance of a red soil-based inorganic coagulant enhanced by Fe3O4 magnetic loading - Yixuan Huang; Qi Li; Ruimin Zhao; Ruyan Luo; Shaman Zhou; Yuanliang Zhang; Jingbao He; Wanqing Yang; Zhifei Yu; Jiahao Yang; Liang He; Xuyuan Zhao; et al. (Process Safety and Environmental Protection, 2026)

Solvent-mediated construction of hydrogen bond networks for boosting the photocatalytic performance of AgBr - Chenyang Wang; Meng Sun; Zhen Tian; Lincai Wang; Dongmei Jiang; Weichi Liu; Qian Liu; Changwen Ma; Ruyan Li (Environmental Research, 2026)

Highly reliable LFIA assay reveals long-term real-world dynamics of neutralizing antibodies against SARS-CoV-2 - Chunxia Chen; Jinbo Wu; Yangguang Ren; Jianing Ji; Ruyan Meng; Zhan Yang; Yan Zhao; Menghan Xue; Xiaoquan Li; Li Wang; Qitong Feng; Jichun Yang; et al. (Science Bulletin, 2026)

Mechanisms of enhanced Cd sequestration by goethite via Zn2+ isomorphic substitution: Structural modulation and surface reactivity - Xiaoyi Sun; Luyao Qin; Lei Yu; Jing Wang; Jiaxiao Liu; Jingze Li; Ruyan Zhou; Meng Wang; Shibao Chen (Journal of Environmental Sciences, 2026)

Ag-O bonding activated cordierite-based photocatalyst enables S-scheme photocatalytic charge separation for enhanced visible-light performance - Lincai Wang; Chentao Ren; Fengshan Yu; Jiashuang Wang; Shichao Xie; Xunwei Ma; Ruyan Li; Weiju Hao; Weihua Gu (Journal of Environmental Chemical Engineering, 2026)

Selenium biofortification modulates the structure, digestion, and microbial fermentation characteristics of tea proteins - Zhiliang Jiang; Fuqing Bai; Wei Guo; Xinyu Wang; Kun Hu; Ranran Liu; Yuxuan Zhang; Ruyan Hou; Hongfang Li; Chuanyi Peng; Minhao Xie; Daxiang Li; et al. (Food Research International, 2026)

YY1 in prostate cancer: multidimensional oncogenicmechanisms and emerging therapeutic vulnerabilities - Qiuyu Liu; Zhongxiu Liang; Lu Li; Ruyan Wen; Linjian Mo; Yonghong Liu; Xueni Wang (Journal of Molecular Histology, 2026)

Correction: PKR Inhibition Prevents Neuroinflammation and Rescues Depressive‑Like Behaviors Via BDNF/TrkB Signaling - Yue Hu; Tahir Ali; Shengnan Mou; Qichao Gong; Ruyan Gao; Yanhua Luo; Shupeng Li; Li Ling; Liangliang Hao (Journal of Neuroimmune Pharmacology, 2026)

Construction of a multifunctional catalyst with bifunctional channel and inner electric field through surface grafting of β-Cyclodextrin - Chenyang Wang; Weichi Liu; Zhen Tian; Lincai Wang; Dongmei Jiang; Qian Liu; Ruyan Li (Journal of Environmental Management, 2025)

Assessing the effect of a non-ionic surfactant on surface degradation of the pesticide Acetamiprid on live tea plants - Wanjun Gao; Xinyi Du; Zili Gao; Haochen Dai; Lanying Li; Bingling Zhang; Gaoxi Wang; Xuejuan Chen; Jeffery Doherty; John M. Clark; Ruyan Hou; Fan Luo; et al. (Food Research International, 2025)

Regional environmental risk thresholds for cadmium in Chinese agricultural soils: Integrating zonal soil types and pedogenic properties - Lei Yu; Meng Wang; Luyao Qin; Xiaoyi Sun; Jing Wang; Jiaxiao Liu; Ruyan Zhou; Jingze Li; Shibao Chen (Science of The Total Environment, 2025)

Effects of desiccation time on performance of a cultured (Neopyropia yezonensis) and fouling alga (Ulva prolifera) - Yifei Shen; Ruyan He; Yuqing Sun; Shuang Li; Yinqing Zeng; Peimin He; Jianheng Zhang (Aquatic Botany, 2025)

Constructing Ag O C bond bridged Z-Scheme AgI/BiOI/CQDs heterojunctions for enhanced tetracycline degradation: Unraveling the role of interfacial charge transfer pathways - Fangming Qian; Zhen Tian; Qian Liu; Dongmei Jiang; Weichi Liu; Ruyan Li (Journal of Environmental Chemical Engineering, 2025)

Temporal trends of the disease burden of renal cell carcinoma from 1992 to 2019 in the US: a population-based analysis - Ruyan Chen; Tian Tang; Jianglong Han; Si Li; Wenmin Liu; Haiyu Deng; Tingting Jian; Zhenming Fu (Cancer Causes & Control, 2025)

Negative impacts of rodents on soil microbial diversity and composition modulated by rainfall intensity in a semiarid steppe - Yunqi Xiong; Zhenzhen Zheng; Baofa Yin; Guoliang Li; Xinrong Wan; Ruyan Qian; Linfeng Li; Shuntian Guan; Yuan Liu; Yanfen Wang; Xiaoyong Cui; Jianqing Du; et al. (Applied Soil Ecology, 2025)

A “three-in-one” detection platform based on cerium-coated metal-organic framework for multimodal glyphosate detection - Fei Tong; Wanqi Jiang; Hui Li; Xiyao Liang; Chuang Jiang; Yaqing Xiao; Xinying Sheng; Ruyan Hou; Xiaochun Wan; Yingnan Liu (Journal of Hazardous Materials, 2025)

Tea storage process: Flavor scalping in green tea caused by plastic packaging materials - Fuqing Bai; Guijie Chen; Yuexin Liu; Zhiwei Liao; Zhiliang Jiang; Yanan Hu; Ruyan Hou; Hongfang Li; Chuanyi Peng; Xiaochun Wan; Huimei Cai (Food Packaging and Shelf Life, 2025)

PKR Inhibition Prevents Neuroinflammation and Rescues Depressive-Like Behaviors via BDNF/TrkB Signaling - Yue Hu; Tahir Ali; Shengnan Mou; Qichao Gong; Ruyan Gao; Yanhua Luo; Shupeng Li; Li Ling; Liangliang Hao (Journal of Neuroimmune Pharmacology, 2025)

Effects of glycation modifications of different glycosylating agents on the molecular structure and gel properties of sheep's hoof gelatin - Yuhan Li; Nanqi Li; Qianqian Song; Ziqiao Zhao; Ruyan Yuan; Jingyun Wang; Shiling Lu; Qingling Wang (Food Hydrocolloids, 2025)

Rapid, in-situ evaluation of sunflower seed freshness and vigor using Raman microspectroscopy scanning of carotenoids - Jingjing Ma; Luyuan Yang; Wenli Gao; Jianglin Chen; Jiawei Li; Long Jin; Ruyan Hou (Food Chemistry, 2024)

Construction and synergistic anti-tumor study of a tumor microenvironment-based multifunctional nano-drug delivery system - Baoqing Liu; Qinghua Zheng; Xiandong Shi; Jian Shen; Ruyan Li; Jiahong Zhou (Journal of Photochemistry and Photobiology B: Biology, 2024)

Alleviation of fluoride-induced colitis by tea polysaccharides: Insights into the role of Limosilactobacillus vaginalis and butyric acid - Chenjun Zhao; Guijie Chen; Ying Huang; Yuxuan Zhang; Sichen Li; Zhiliang Jiang; Huihui Peng; Juan Wang; Daxiang Li; Ruyan Hou; Chuanyi Peng; Xiaochun Wan; et al. (Journal of Hazardous Materials, 2024)

One-step synthesis of oxygen vacancy-rich BiOBr/TiO2 composite: Ultrafast adsorption-photocatalytic performance and mechanism - Xiaozhen Zhang; Xirong Gu; Yanhua Song; Ruyan Xie; Shuzhe Zhang; Jingyao Li; Shihou Sheng; Haifeng Zou (Chemical Engineering Journal, 2024)

Effects of Potassium Fertilizer Base/Topdressing Ratio on Dry Matter Quality, Photosynthetic Fluorescence Characteristics and Carbon and Nitrogen Metabolism of Potato - Jiali Xie; Ming Li; Mingfu Shi; Yichen Kang; Ruyan Zhang; Yong Wang; Weina Zhang; Shuhao Qin (Potato Research, 2024)

Understanding the effect of plastic food packaging materials on food flavor: A critical review - Fuqing Bai; Guijie Chen; Yanan Hu; Yuexin Liu; Ruirui Yang; Junsheng Liu; Ruyan Hou; Hongfang Li; Xiaochun Wan; Huimei Cai (Trends in Food Science & Technology, 2024)

Effects of the combined use of kaolinite and dolomite as catalysts for the heavy oil oxidation - Yanqiu Dai; Xianghui Zhang; Runlin Pu; Wei Hu; Ling Wang; Huan Yang; Wenlin Yang; Qin Liu; Ruyan Wang; Zhongquan Li; Qian Feng (Applied Clay Science, 2024)

A facile fluorescence microplate immunoassay based on an in situ fluorogenic reaction for the detection of two highly toxic anticoagulant rodenticides in food and biological matrix - Hongfang Li; Jie Chen; Wenqing Xu; Baowei Huang; Chuanyi Peng; Huimei Cai; Ruyan Hou; Kai Wen; Lin Li; Baolei Dong; Zhanhui Wang (Food Chemistry, 2024)

The mechanism of alkali-induced rice protein gel formation: Effect of alkali concentration and temperature - Yaoyao Lian; Ya Li; Ruyan Lv; Lifeng Wang; Wenfei Xiong (Food Hydrocolloids, 2024)

Effects of extra-extreme precipitation variability on multi-year cumulative nitrous oxide emission in a semiarid grassland - Linfeng Li; Yanbin Hao; Weijin Wang; Joel A. Biederman; Zhenzhen Zheng; Yanfen Wang; Muyesaier Tudi; Ruyan Qian; Biao Zhang; Rongxiao Che; Xiaoning Song; Xiaoyong Cui; et al. (Agricultural and Forest Meteorology, 2023)

Lipidomic profiling study on neurobehavior toxicity in zebrafish treated with aflatoxin B1 - Zishuang Wang; Xiabing Li; Tiancai Wang; Guangqin Liao; Jingyi Gu; Ruyan Hou; Jing Qiu (Science of The Total Environment, 2023)

Tracing the origin of Taiping Houkui green tea using 1H NMR and HS-SPME-GC–MS chemical fingerprints, data fusion and chemometrics - Ge Jin; Yuanyuan Zhu; Chuanjian Cui; Chen Yang; Shaode Hu; Huimei Cai; Jingming Ning; Chaoling Wei; Aoxia Li; Ruyan Hou (Food Chemistry, 2023)

TiO2/PVA Based Composites: Visible Light Activated Rapid Dual-Mode optical Response - Fangke Wang; Yanhua Song; Ruyan Xie; Jingyao Li; Xiaozhen Zhang; Haijiao Xie; Haifeng Zou (Chemical Engineering Journal, 2023)

Analysis of the Interannual Variability of Pacific Swell Pools - Xin Zhang; Kejian Wu; Rui Li; Dongze Li; Shuai Zhang; Ruyan Zhang; Shuo Li; Xianghui Dong (Journal of Marine Science and Engineering, 2023)
The investigation of the propagation of swells throughout the ocean has long been a subject of significant interest in physical oceanography. This paper investigates the interannual variability of the Pacific swell pools and examines the factors contributing to their formation using the European Centre for Medium-Range Weather Forecasts (ECMWF) ERA5 re-analysis dataset. Our results show that the interaction between swell propagation and wind fields influences the formation and development of Pacific swell pools. The eastern and southern Pacific swell pools are mainly caused by the northward propagation of swells from the South Pacific; the western and northern swell pools are primarily influenced by the southward propagation of swells from the North Pacific; and the central part of the swell pools is the result of the combined impact of both swell propagation from the north and south Pacific. The size of the swell pools in the Pacific Ocean is at its maximum in the northern hemisphere during the winter (December, January, and February) and at its minimum during the summer (June, July, and August). Due to the impact of the low-pressure systems, the swell pools in the winter hemisphere are relatively small, while the swell pools in the summer hemisphere are significantly larger. There is a relationship between the swell pools and ENSO events. When an El Niño event (La Niña event) occurs, the swells propagating to the low latitudes of the Pacific Ocean from high latitudes will strengthen (weaken), resulting in an increase (decrease) in the size of the swell pools. Analyzing the spatial and temporal distribution of the swell pools is important for understanding the large-scale effect of waves.

Relationship between Large-Scale Variability of North Pacific Waves and El Niño-Southern Oscillation - Xin Zhang; Kejian Wu; Rui Li; Shuai Zhang; Ruyan Zhang; Jin Liu; Alexander V. Babanin (Journal of Marine Science and Engineering, 2023)
Ocean waves are crucial for driving various oceanic processes. In this study, the spatial and temporal distribution of significant wave height (SWH) in the North Pacific (NP) is analyzed using the 42-year ERA5 reanalysis dataset from European Centre for Medium-Range Weather Forecasts (ECMWF). The presence of an ENSO signal is confirmed in wave fields of the North Pacific. Furthermore, the spatial distributions of swells and wind waves are analyzed using the Empirical Orthogonal Function (EOF) method, revealing that waves can transport large-scale signals from the NP to lower latitudes through swells. In addition, our research reveals a relationship between ENSO and Stokes drift in the NP. Stokes drift contributes positively to the maintenance of stable sea surface temperatures (SSTs) by transporting more (less) water towards the equatorial Pacific during El Niño (La Niña year) years. It is further noted that during strong ENSO events, the strength of the Stokes drift anomaly intensifies accordingly, which implies a strong link between wave-induced transport and ENSO.

Partial Substitution of Chemical Fertilizer with Organic Manure Enhances Yield Attributes and Tuber Quality in Potato - Mingfu Shi; Aixia Guo; Yichen Kang; Weina Zhang; Yanling Fan; Xinyu Yang; Ruyan Zhang; Yong Wang; Yajie Li; Shuhao Qin (Journal of Soil Science and Plant Nutrition, 2023)

A near-infrared photoelectrochemical aptasensing system based on Bi2O2S nanoflowers and gold nanoparticles for high-performance determination of MCF-7 cells - Xingxing Xu; Zihan Ding; Xue Zhang; Ruyan Zha; Wei Li; Lian Xu; Dong Sun; Xiaojun Cai; Tao Liang; Yanying Wang; Chunya Li (Analytica Chimica Acta, 2023)

Catalytic capacity evolution of montmorillonite in in-situ combustion of heavy oil - Xianghui Zhang; Junjie Wang; Ling Wang; Zhongquan Li; Wei Hu; Yanqiu Dai; Yuanyu Kou; Shengjun Lei; Qian Li; Wen Zhang; Hongkui Li; Ruyan Wang; et al. (Fuel, 2023)

Energy substrate metabolism and oxidative stress in metabolic cardiomyopathy - Ze Chen; Zhao-Xia Jin; Jingjing Cai; Ruyan Li; Ke-Qiong Deng; Yan-Xiao Ji; Fang Lei; Huo-Ping Li; Zhibing Lu; Hongliang Li (Journal of Molecular Medicine, 2022)

Selective TAAR1 agonists induce conditioned taste aversion - Jianfeng Liu; Ruyan Wu; Bernard Johnson; Yanan Zhang; Qing Zhu; Jun-Xu Li (Psychopharmacology, 2022)

The selective TAAR1 partial agonist RO5263397 promoted novelty recognition memory in mice - Ruyan Wu; Jianfeng Liu; Robert Seaman; Bernard Johnson; Yanan Zhang; Jun-Xu Li (Psychopharmacology, 2021)

Irrigation with Magnetized Water Affects the Soil Microenvironment and Fruit Quality of Eggplants in a Covered Vegetable Production System in Shouguang City, China - Haoran Cui; Xiumei Liu; Ruyan Jing; Mingzhong Zhang; Lu Wang; Li Zheng; Linggang Kong; Huatian Wang; Fengyun Ma (Journal of Soil Science and Plant Nutrition, 2020)

Terrestrial N 2 O emissions and related functional genes under climate change: A global meta‐analysis - Linfeng Li; Zhenzhen Zheng; Weijin Wang; Joel A. Biederman; Xingliang Xu; Qinwei Ran; Ruyan Qian; Cong Xu; Biao Zhang; Fang Wang; Shutong Zhou; Lizhen Cui; et al. (Global Change Biology, 2020)
Nitrous oxide (N 2 O) emissions from soil contribute to global warming and are in turn substantially affected by climate change. However, climate change impacts on N 2 O production across terrestrial ecosystems remain poorly understood. Here, we synthesized 46 published studies of N 2 O fluxes and relevant soil functional genes (SFGs, that is, archaeal amoA , bacterial amoA , nosZ , narG , nirK and nirS ) to assess their responses to increased temperature, increased or decreased precipitation amounts, and prolonged drought (no change in total precipitation but increase in precipitation intervals) in terrestrial ecosystem (i.e. grasslands, forests, shrublands, tundra and croplands). Across the data set, temperature increased N 2 O emissions by 33%. However, the effects were highly variable across biomes, with strongest temperature responses in shrublands, variable responses in forests and negative responses in tundra. The warming methods employed also influenced the effects of temperature on N 2 O emissions (most effectively induced by open‐top chambers). Whole‐day or whole‐year warming treatment significantly enhanced N 2 O emissions, but daytime, nighttime or short‐season warming did not have significant effects. Regardless of biome, treatment method and season, increased precipitation promoted N 2 O emission by an average of 55%, while decreased precipitation suppressed N 2 O emission by 31%, predominantly driven by changes in soil moisture. The effect size of precipitation changes on nirS and nosZ showed a U‐shape relationship with soil moisture; further insight into biotic mechanisms underlying N 2 O emission response to climate change remain limited by data availability, underlying a need for studies that report SFG. Our findings indicate that climate change substantially affects N 2 O emission and highlights the urgent need to incorporate this strong feedback into most climate models for convincing projection of future climate change.

Automatic sub-pixel coastline extraction based on spectral mixture analysis using EO-1 Hyperion data - Zhonghua Hong; Xuesu Li; Yanling Han; Yun Zhang; Jing Wang; Ruyan Zhou; Kening Hu (Frontiers of Earth Science, 2019)

Toll of Mental Disorders: TLR-Mediated Function of the Innate Immune System - Jian-Feng Liu; Ruyan Wu; Jun-Xu Li (Neuroscience Bulletin, 2019)

A possible mechanism for the occurrence of wintertime extreme precipitation events over South China - Wenyu Huang; Zifan Yang; Xinsheng He; Daiyu Lin; Bin Wang; Jonathon S. Wright; Ruyan Chen; Wenqian Ma; Feifei Li (Climate Dynamics, 2019)

Using wavelet analysis of hyperspectral remote-sensing data to estimate canopy chlorophyll content of winter wheat under stripe rust stress - Ruyan He; Hui Li; Xiaojun Qiao; Jinbao Jiang (International Journal of Remote Sensing, 2018)

Leaching of Cu, Cd, Pb, and phosphorus and their availability in the phosphate-amended contaminated soils under simulated acid rain - Hongbiao Cui; Shiwen Zhang; Ruyan Li; Qitao Yi; Xuebo Zheng; Youbiao Hu; Jing Zhou (Environmental Science and Pollution Research, 2017)

Imbalanced functional link between reward circuits and the cognitive control system in patients with obsessive-compulsive disorder - Chunming Xie; Lisha Ma; Nan Jiang; Ruyan Huang; Li Li; Liang Gong; Cancan He; Chaoyong Xiao; Wen Liu; Shu Xu; Zhijun Zhang (Brain Imaging and Behavior, 2017)